Running from Paris to Beijing: biomechanical and physiological consequences - Millet, G. Y.; Morin, J.-B.; Degache, F.; Edouard, P.; Feasson, L.; Verney, J.; Oullion, R. (European Journal of Applied Physiology, 2009)
The purpose of this study was to examine the physiological and biomechanical changes occurring in a subject after running 8,500 km in 161 days (i.e. 52.8 km daily). Three weeks before, 3 weeks after (POST) and 5 months after (POST+5) running from Paris to Beijing, energy cost of running (Cr), knee flexor and extensor isokinetic strength and biomechanical parameters (using a treadmill dynamometer) at different velocities were assessed in an experienced ultra-runner. At POST, there was a tendency toward a `smoother` running pattern, as shown by (a) a higher stride frequency and duty factor, and a reduced aerial time without a change in contact time, (b) a lower maximal vertical force and loading rate at impact and (c) a decrease in both potential and kinetic energy changes at each step. This was associated with a detrimental effect on Cr (+6.2%) and a loss of strength at all angular velocities for both knee flexors and extensors. At POST+5, the subject returned to his original running patterns at low but not at high speeds and maximal strength remained reduced at low angular velocities (i.e. at high levels of force). It is suggested that the running pattern changes observed in the present study were a strategy adopted by the subject to reduce the deleterious effects of long distance running. However, the running pattern changes could partly be linked to the decrease in maximal strength.